Comparison of Foundation by Direct Shear Test in Different Soil Condition - Jung K.C., Kushal; Poudel, Peshal; Lamichhane, Niraj; Bhat, Jeewan; Sharma, Prasang (International Journal on Engineering Technology, 2024)
In this paper, we mainly focused on the comparison of foundation in two different locations. Size of foundation depends on bearing capacity of soil. Standard proctor test has been conducted to determine Optimum Moisture Content (OMC) of soil and Direct shear test has been conducted to determine the shear strength parameters in OMC. Bearing capacity of soil is calculated from shear strength parameters using Terzaghi’s equation. Area of foundation is calculated and it is found that area differ by 34.47% at two locations.